(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The purpose of this study is to develop an accurate, simple, and fast reverse-phase high-performance liquid chromatographic (RP-HPLC) method and validate for analyzing organic impurities in osimertinib mesylate (OSM) tablets. The developed method separates and validated for chloro impurity, hydroxy impurity, methoxy impurity, des-acrylic acid impurity, N-oxide, OSM dimer and OSM. The separation of all these impurities were achieved on inert sustain C18 (4.6×250) mm, 3 μ column, The mobile phase consists of 0.1% formic acid with pH to 6.50 adjusted with ammonium hydroxide and acetonitrile delivered in gradient elution mode. The analytes were monitored at 268 nm. Stress studies were performed to evaluate the capability of stability-indicating of this method. The OSM was observed to be stable under thermal, photolytic and neutral conditions. However, it is labile under acidic, basic and oxidative conditions. All the degradants are well resolved form the principle peak OSM. All the major degradation products were isolated and characterized through UHPLC-IMS-Q-TOF-MS. The method was validated as per International Conference on Harmonization (ICH) guidelines, and the validation included specificity, limit of detection (LoD), limit of quantification (LoQ), linearity, accuracy, precision, robustness, and solution stability for isolated impurities and OSM. The method was developed for this drug product with the purpose of properly defining the quality specification of the drug product or drug substance. This method can be incorporated in the monographs of USP, EP/BP, IP etc.